مدى استخدام الوسائل التثقيفية في مراكز الرعاية الصحية الأولية في مدينة اللاذقية - طويل, علاء; صالح, ليندا; علي, مروى (Latakia University Journal -Medical Sciences Series, 2017)
شهد القرن الماضي تطوراً كبيراً في جميع المجالات, فقد أخذت خدمات الرعاية الصحية تتطور باستمرار ومن ضمنها التثقيف الصحي باعتباره حجر الزاوية في الوقاية من الأمراض و يبدأ من مراكز الرعاية الصحية الأولية المسؤولة عن ضمان توفير التوعية الصحية ليس فقط للمرضى وعائلاتهم وإنما أيضاً للمجتمع بأسره, وحتى يحقق التثقيف الصحي في المراكز الصحية غايته المنشودة لا بد من دعمه باستخدام وسائل التثقيف الصحي الملائمة التي تسهم إسهاماً فعالاً في رفع مستوى العملية التثقيفية و زيادة كفاءتها, فالاستخدام الأمثل لوسائل التثقيف بوساطة الشخص الكفء سوف يساعد هذا الشخص على أداء عمله بكفاءة عالية وجودة فائقة, وكذلك فإن الوسائل التثقيفية تساعد على تقديم المعلومة الصحية بأسلوب مشوق وتستطيع أن تخلق جواً من التفاعل والعمل الجماعي بين مقدم المعلومة والمستفيد.بالرغم من أهمية استخدام وسائل التثقيف الصحي في عملية التثقيف الصحي, إلا أنه هناك قلة في الدراسات الأجنبية والعربية و لا يوجد دراسات في سوريا تعنى بهذا الجانب الهام من عملية التثقيف الصحي, لذلك هدفت هذه الدراسة إلى تقييم مدى استخدام وسائل التثقيف الصحي في مراكز الرعاية الصحية الأولية في مدينة اللاذقية من قبل كافة أفراد الكادر التمريضي العامل في تلك المراكز حيث أن كل عنصر تمريضي مقدم للرعاية الصحية يلعب دوره كمثقف صحي أثناء تقديم الخدمات الصحية.أجريت الدراسة في مراكز الرعاية الصحية الأولية في مدينة اللاذقية, حيث تكونت العينة من 220عنصر تمريضي مقدم للرعاية الصحية الأولية موزعين على 12 مركز صحي. وكانت أهم النتائج أن مقدمي الرعاية الصحية يستخدمون الوسائل التثقيفية المتاحة لهم في المركز, ولكن هناك نقص ملحوظ في توافر الوسائل التثقيفية السمعية والسمعية البصرية والحسية, كما أن مقدمي الرعاية الصحية يدركون أهمية استخدام الوسائل التثقيفية في عملية تقديم المعلومة الصحية وأهميتها للمستفيد ولكن هناك العديد من الصعوبات التي تواجههم حيال ذلك.The last century has witnessed a great development in all areas, Health care services are constantly evolving including health education which is considered as a cornerstone in the prevention of diseases. Health education should start from primary health care centers which are responsible for ensuring the provision of health education not only for patients and their families but also to society as a whole. In order to achieve the desired objectives of health education in health centers, it must be desired supported by using the appropriate materials of health education, which effectively contribute to raising the educational process level and increase its efficiency. The optimal use of educational materials by competent person will help him to do his job efficiently with high quality. Educational materials helps in providing health information in interesting manner and create an ambiance of interaction and teamwork between the provider and beneficiary. Despite the importance of using health education materials in the process of providing health information , there are few foreign and Arabic studies and there are no studies in Syria that deal with this important side of health education process ( i.e : the use of educational materials). This study aimed to evaluate the use of health educational materials in primary healthcare centers in the city of Lattakia by all members of the nursing staff working in those centers, since each nursing health care provider plays a role as a health educator during the delivery of health services.The study was conducted in primary health care centers in the city of Lattakia , The sample consisted of 220 nursing and health care providers in 12 health center. The most important results were that health care providers use the educational materials available to them at the center, and there is a remarkable shortage in the availability of audio visual and sensual educational materials. Health care providers acknowledge the importance of using educational materials in the process of providing health information to the beneficiary. However, There are many difficulties facing them.